Cue-Induced Brain Activation in Chronic Ketamine-Dependent Subjects, Cigarette Smokers, and Healthy Controls: A Task Functional Magnetic Resonance Imaging Study - Liao, Yanhui; Johnson, Maritza; Qi, Chang; Wu, Qiuxia; Xie, An; Liu, Jianbin; Yang, Mei; Huang, Maifang; Zhang, Yan; Liu, Tieqiao; Hao, Wei; Tang, Jinsong (Frontiers in Psychiatry, 2018)
Background Observations of drug-related cues may induce craving in drug-dependent patients, prompting compulsive drug-seeking behavior. Sexual dysfunction is common in drug users. The aim of the study was to examine regional brain activation to drug (ketamine, cigarette smoking) associated cues and natural (sexual) rewards. Methods A sample of 129 (40 ketamine use smokers (KUS), 45 non-ketamine use smokers (NKUS) and 44 non-ketamine use non-smoking healthy controls (HC)) participants underwent functional magnetic resonance imaging (fMRI) while viewing ketamine use related, smoking and sexual films. Results We found that KUS showed significant increased activation in anterior cingulate cortex and precuneus in response to ketamine cues. Ketamine users (KUS) showed lower activation in cerebellum and middle temporal cortex compared with non-ketamine users (NKUS and HC) in response to sexual cues. Smokers (KUS and NKUS) showed higher activation in the right precentral frontal cortex in response to smoking cues. Non-ketamine users (NKUS and HC) showed significantly increased activation of cerebellum and middle temporal cortex while viewing sexual cues. Conclusions These findings clearly show the engagement of distinct neural circuitry for drug-related stimuli in chronic ketamine users. While smokers (both KUS and NKUS) showed overlapping differences in activation for smoking cues, the former group showed a specific neural response to relevant (i.e. ketamine-related) cues. In particular, the heightened response in anterior cingulate cortex may have important implications for how attentionally salient such cues are in this group. Ketamine users (KUS) showed lower activation in response to sexual cues may partly reflect the neural basis of sexual dysfunction.